The Impact of Aerobic Dance Intensity on Blood Pressure Reduction in Physically Active Elderly Women - Poppy Elisano Arfanda; Ians Aprilo; Arimbi; Noortje Anita Kumaat; Heryanto Nur Muhammad (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the relationship between aerobic dance intensity and blood pressure reduction in active elderly women who routinely participate in community exercise programs. The research design used is correlational with a quantitative approach. The sample consists of members of the aerobic dance community in Taman Pakui Sayang (TPS), Makassar, comprising 20 elderly women aged 45–59 years who participate in aerobic dance at least twice a week for 8 weeks. Data were collected through blood pressure measurements before and after the intervention, as well as monitoring exercise intensity using the Borg RPE (Rating of Perceived Exertion) Scale. The results of the analysis showed a significant negative correlation between aerobic dance intensity and a decrease in systolic with r = -0.62; p = 0.001 and diastolic (r = -0.55; p = 0.004) blood pressure. These findings indicate that the higher the intensity of the exercise performed, the greater the decrease in blood pressure that occurs. Thus, moderate to high intensity aerobic dance can be an effective non-pharmacological strategy in the management of hypertension in elderly women.